RISK FACTOR OF EXLUSIVE BREASTFEEDING AND INFECTIVE DISEASES ON STUNTING INCINDANCE - erma nurlita sari; Linda Dewanti; Widati Fatmaningrum (Indonesian Midwifery and Health Sciences Journal, 2022)
Background: Stunting one of the nutritional problems in the children under five wich has an impact on the distruption of children’s growth. The long-term impact will reduce the quality of Indonesian children in the future. Stunting is closed to first 1000 days of life. Many factos influence. Methode: The research method used in this research is observational analytic with case control approach. The sample was using simple random sampling. The number of sampels in the study were the age 6-36 month. 45 as cases and 45tooddler as control. The dependen variable in this study was stunting and the variable was history of exclusive breastfeeding, age of first complementary feeding, incidence of diarrhea and acut respiration disesase  infection (ARI),. Collecting data through primary and secondary data. Statistis test by chi square, t-test Independen and regresi logistic Result: The result showed history of exclusive breastfeeding test a value of p=0,010, incidence of diarrhea with a value of p=0,017 and history of ARI disease with a value of p=0,017, it shows that there is a relationship between the incidence of stuntingnin children age 6-36 month. The multivariate analys with logistic regression test result showed that there was the most relationtship with stunting are between a history of exclusive breastfeeding with OR=0.042 history of diarrhea incidence with OR=0.042, history of ARI disease with OR=6.627 and Conclusions: The data on the result of the study showed that a history of exclusive breastfeeding, incidence of diarrhea, history of ARI disease has a significant relation with stunting..   keyword :  stunting, exclusive breastfeeding, history of child infection.